Corporate social responsibility in the textile sector: A conceptual analysis of dimensions - Luque González, Arturo; Herrero-García, Noelia (Opción, 2019)
social responsibility (CSR), it is difficult to define this macro-concept. This article proposes the use of a qualitative methodology that limits the available definitions through an analysis determined by their frequency of use in Google Scholar. The sequential coding of these constructs is saturated in six categories. A triad model is proposed, from which the economic-social-ethical combination emerges as being cited once in every two occasions. The results show that the environmental and labor dimensions have a residual frequency of use, and this finding may be used to address weaknesses in CSR process